Boundedness in a Biofilm-Chemotaxis Model in Evolving Porous Media. Issue 6 (2nd November 2017) - Schulz, Raphael
Abstract: The article concerns with a model discribing the growth of a biofilm made by chemotactical bacteria within a saturated porous media and affects the flow through the pores. The underlying model describing this process on the macroscale is derived in [21]. Therein also solvability in a weak sense and boundedness of solutions with high regularity is investigated. This current paper verifies the existence of bounded weak solutions in case of less regularity assumptions on the data.